Upaya Pengendalian Bahan Kimia Berbahaya pada Proses Pengecatan Pagar di UD.X - Permatasari, Eska Distia (Jurnal Skala Kesehatan, 2026)
The industry in the informal sector that has an important role is the welding industry. In the fence making process, there is a painting process that contains chemicals that have an impact on health. The purpose of this study was to determine the dangers of chemicals used in the fence painting process. The research method used was qualitative by using data collection techniques in the form of observation and interviews carried out at the UD. X workshop. From the results of the study, there were dangers of chemicals in the fence painting process such as nippon paint zinc chromate primer, nippon paint A special thinner, nippon paint nippe 2000, avian (wood and iron paint), danapaint top color, danapaint danalac, emco luc, alfaglos polyster putty. It can be concluded that the welding industry, especially in the iron fence painting process, has a risk of exposure to hazardous chemicals that can cause health problems such as headaches (dizziness), coughs, flu, and asthma to the risk of serious diseases such as lung cancer. Therefore, it is important for the workshop to increase hazard control efforts by using a control hierarchy.